2013
DOI: 10.1002/app.40015
|View full text |Cite
|
Sign up to set email alerts
|

Nylon 66 nanofibers prepared by CO2 laser supersonic drawing

Abstract: Nylon 66 nanofibers were prepared by irradiating as-spun nylon 66 fibers with radiation from a carbon dioxide (CO 2 ) laser while drawing them at supersonic velocities. A supersonic jet was generated by blowing air into a vacuum chamber through the fiber injection orifice. The fiber diameter depended on the drawing conditions used, such as laser power, chamber pressure, laser irradiation point, and fiber supply speed. A nanofiber obtained at a laser power of 20 W and a chamber pressure of 20 kPa had an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…T m2 was also observed in the DSC curve of PET and nylon 66 nanofibers as previously reported [14,16]. The nanofibers produced by CLSCMD thus exhibit T m2 , which is a unique feature.…”
Section: Relationship Between Superstructure Of Nanofiber Sheet and Dsupporting
confidence: 72%
See 1 more Smart Citation
“…T m2 was also observed in the DSC curve of PET and nylon 66 nanofibers as previously reported [14,16]. The nanofibers produced by CLSCMD thus exhibit T m2 , which is a unique feature.…”
Section: Relationship Between Superstructure Of Nanofiber Sheet and Dsupporting
confidence: 72%
“…CLSD has already been applied to prepare nanofibers of poly(Llactic acid) [1], poly(ethylene terephthalate) (PET) [11], poly(ethylene-2,6-naphthalate) [12], ethylene tetrafluoroethylene [13], nylon 66 [14], and poly(phenylene sulfide) [15]. The nanofibers obtained are infinitely long because large plastic deformation accompanied by stable necking occurs during CLSD.…”
Section: Introductionmentioning
confidence: 99%
“…CLSD employs only CO 2 laser irradiation and does not require additional processes or solvents, unlike electrospinning, which requires a solvent, or sea-island-type conjugated melt spinning that requires the removal of a second component. CLSD has already been applied to prepare NFs of poly(L-lactic acid) (PLLA) [24], poly(ethylene terephthalate) (PET) [25], poly(ethylene-2,6-naphthalate) [26], poly(glycolic acid) (PGA) [27], ethylene tetrafluoroethylene copolymer [28], nylon 66 [29], and poly(phenylene sulfide) [30].…”
Section: Introductionmentioning
confidence: 99%
“…In our research on the production of nylon 66 nanofibers by CLSD, we have reported that nylon 66 nanofibers were obtained that contained crystals having a melting temperature10-15 C higher than that ordinarily observed for nylon 66 15) . The quantity of such crystals having a higher melting temperature is related to the molecular orientation and an increase in the trans/gauche ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The conditions for preparation nanofiber sheets by CLSMD were determined in reference to those for preparation single nylon 66 nanofibers using the CLSD system 15) . Table 2 compares the drawing conditions used for preparation nylon 66 nanofibers with the CLSMD and CLSD systems.…”
Section: Nanofiber Sheet Preparation Conditionsmentioning
confidence: 99%